Clinical and cost effectiveness of single stage compared with two stage revision for hip prosthetic joint infection (INFORM): pragmatic, parallel group, open label, randomised controlled trial. (31st October 2022) - Blom, Ashley W; Lenguerrand, Erik; Strange, Simon; Noble, Sian M; Beswick, Andrew D; Burston, Amanda; Garfield, Kirsty; Gooberman-Hill, Rachael; Harris, Shaun R S; Kunutsor, Setor K; Lane, J Athene; MacGowan, Alasdair; et al.
Abstract: Objectives: To determine whether patient reported outcomes improve after single stage versus two stage revision surgery for prosthetic joint infection of the hip, and to determine the cost effectiveness of these procedures. Design: Pragmatic, parallel group, open label, randomised controlled trial. Setting: High volume tertiary referral centres or orthopaedic units in the UK (n=12) and in Sweden (n=3), recruiting from 1 March 2015 to 19 December 2018. Participants: 140 adults (aged ≥18 years) with a prosthetic joint infection of the hip who required revision (65 randomly assigned to single stage and 75 to two stage revision). Interventions: A computer generated 1:1 randomisation list stratified by hospital was used to allocate participants with prosthetic joint infection of the hip to a single stage or a two stage revision procedure. Main outcome measures: The primary intention-to-treat outcome was pain, stiffness, and functional limitations 18 months after randomisation, measured by the Western Ontario and McMasters Universities Osteoarthritis Index (WOMAC) score. Secondary outcomes included surgical complications and joint infection. The economic evaluation (only assessed in UK participants) compared quality adjusted life years and costs between the randomised groups. Results: The mean age of participants was 71 years (standard deviation 9) and 51 (36%) were women. WOMAC scores did not differ between groups at 18 months (mean difference 0.13 (95% confidence interval −8.20 to 8.46), P=0.98); however, the single stage procedure was better at three months (11.53 (3.89 to 19.17), P=0.003), but not from six months onwards. Intraoperative events occurred in five (8%) participants in the single stage group and 20 (27%) in the two stage group (P=0.01). At 18 months, nine (14%) participants in the single stage group and eight (11%) in the two stage group had at least one marker of possible ongoing infection (P=0.62). From the perspective of healthcare providers and personal social services, single stage revision was cost effective with an incremental net monetary benefit of £11 167 (95% confidence interval £638 to £21 696) at a £20 000 per quality adjusted life years threshold (£1.0; 1.1; €1.4). Conclusions: At 18 months, single stage revision compared with two stage revision for prosthetic joint infection of the hip showed no superiority by patient reported outcome. Single stage revision had a better outcome at three months, fewer intraoperative complications, and was cost effective. Patients prefer early restoration of function, therefore, when deciding treatment, surgeons should consider patient preferences and the cost effectiveness of single stage surgery. Trial registration: ISRCTN registry ISRCTN10956306 .